Abstracts - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2014)
A Randomized Clinical Trial Comparing Methotrexate and Mycophenolate Mofetil for Noninfectious Uveitis Rathinam SR, Babu M, Thundikandy R, Kanakath A, Nardone N, Esterberg E, Lee SM, Enanoria WTA, Porco TC, Browne EN, Weinrib R, Acharya NR Ophthalmology 2014; 121: 1863–70.